2013
DOI: 10.1371/journal.pone.0081591
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Causes of Recent Warming of Mediterranean Waters. How Much Could Be Attributed to Climate Change?

Abstract: During the past two decades, Mediterranean waters have been warming at a rather high rate resulting in scientific and social concern. This warming trend is observed in satellite data, field data and model simulations, and affects both surface and deep waters throughout the Mediterranean basin. However, the warming rate is regionally different and seems to change with time, which has led to the question of what causes underlie the observed trends. Here, we analyze available satellite information on sea surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 24 publications
6
70
0
Order By: Relevance
“…Our results for the Balearic Sea agree with others who have observed a marked warming of the Mediterranean Sea in the last three decades (Skliris et al, 2012) and are consistent with their hypothesis that the warming of the western Mediterranean could be induced by the warming of the Atlantic inflow related to the Atlantic Multidecadal Oscillation (AMO) (Macías et al, 2013) combined with increasing concentrations of greenhouse gases produced by human activities. Macías et al (2013) concluded that 58% of the recent warming in Mediterranean waters could be attributed to the AMO oscillation, whilst anthropogenic-induced climate change was only responsible for 42% of the total trend. The acceleration of the warming observed in the Mediterranean during the 1990s could be caused, according to them, by a superimposition of anthropogenic-induced warming with the positive phase of the AMO.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results for the Balearic Sea agree with others who have observed a marked warming of the Mediterranean Sea in the last three decades (Skliris et al, 2012) and are consistent with their hypothesis that the warming of the western Mediterranean could be induced by the warming of the Atlantic inflow related to the Atlantic Multidecadal Oscillation (AMO) (Macías et al, 2013) combined with increasing concentrations of greenhouse gases produced by human activities. Macías et al (2013) concluded that 58% of the recent warming in Mediterranean waters could be attributed to the AMO oscillation, whilst anthropogenic-induced climate change was only responsible for 42% of the total trend. The acceleration of the warming observed in the Mediterranean during the 1990s could be caused, according to them, by a superimposition of anthropogenic-induced warming with the positive phase of the AMO.…”
Section: Discussionsupporting
confidence: 93%
“…This rate is consistent with the trend obtained for the SST, where a lower rate (0.026 ºC/year) has been registered for the period 1985-2009, which translates into an overall increase of 0.7 ºC in 25 years. The annual warming rate in SST is in agreement with the findings of Nykjaer (2009), López García and Camarasa (2011) and Skliris (2012) for the western Mediterranean, who gave a rate of about 0.03 ºC/year for about the same period; and with the trends given by Macías et al (2013) for the whole Mediterranean (0.037 ºC/year). Although the warming of the climate system since the middle of the 19th century is accepted by almost all scientists, the observed trends in oceanic SST differ depending on the ocean, the period of reference and also the database employed in the analysis.…”
Section: Discussionsupporting
confidence: 91%
“…However, on such decadal time scales future change will be dominated by natural variability of the climate system which is challenging to predict with the current climate modeling tools (Meehl et al, 2009;O'Kane et al, 2013;Risbey et al, 2014). This results in a mismatch in temporal scale between what the models can deliver and the relevant time-window for ecological considerations (Massom and Stammerjohn, 2010;Macias et al, 2013;Supplementary Table 1).…”
Section: Key Challenges and Recommendationsmentioning
confidence: 99%
“…However, from an ecological perspective, shorter (<30 years) time frames are key due to biological processes, including life cycles, generation lengths and phenology (Stock et al, 2011), and the time frames of human activities (such as fishing) and political decision-making. At these shorter temporal scales it is difficult or impossible to distinguish between natural variability and the background climate change signal (Macias et al, 2013). Furthermore, many key ecological processes occur at regional (i.e., tens to hundreds of kilometers in extent) or smaller scales, hence biological responses to change also vary at these scales (Helmuth et al, 2006;Clarke et al, 2009;Peck, 2011;Chave, 2013).…”
mentioning
confidence: 99%
“…Similar migrations were recently reported off the northern Tunisian coast but they rather concerned teleost species , Ben Souissi et al 2011 Records of alien species and especially those described in this paper are consistent with data provide by Ben Rais Lasram and Mouillot (2009) who noted a signifi cant increase of species incoming to the Mediterranean Sea from the Red Sea and eastern tropical Atlantic. Such intrusions are due to the fact that the waters of this sea are becoming warmer for several decades now (Francour et al 1994, Golani 1998, Dulčić and Grbec 2000, Macias et al 2013). The new Mediterranean fi ndings of M. japanica extend the distribution of the species, and increase the number of fi sh species in this sea, but also in the Tunisian waters, where captures of 11 specimens showed that the species should considered as locally present, but other records are needed to state if a sustainable population inhabits the area, M. japanica being a large migratory species .…”
mentioning
confidence: 99%